Those stubborn roots

Algebra Level 3

x + 3 x + x + 3 + x 3 x x 3 = x \frac{x+\sqrt 3}{\sqrt x +\sqrt{x+\sqrt 3}}+\frac{x-\sqrt{3}}{\sqrt x -\sqrt{x-\sqrt3}} = \sqrt x If x x is a positive integer satisfying the above expression, find the value of x x .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Oct 29, 2017

x + 3 x + x + 3 + x 3 x + x 3 = x Let a = x + 3 , b = x 3 a x + a + b x b = x a ( x a ) ( x + a ) ( x a ) + b ( x + b ) ( x b ) ( x + b ) = x a ( x a ) x a + b ( x + b ) x b = x Note that x a = 3 , x b = 3 a ( x a ) 3 + b ( x + b ) 3 = x ( b a ) x + a a + b b = 3 x Note that b a = 2 3 2 3 x + a a + b b = 3 x a a + b b = 3 3 x Squaring both sides a 3 + b 3 + 2 a b a b = 27 x Putting back a = x + 3 , b = x 3 ( x + 3 ) 3 + ( x 3 ) 3 + 2 ( x 2 3 ) 3 2 = 27 x 2 x 3 + 18 x + 2 x 6 9 x 4 + 27 x 2 27 = 27 x 2 x 6 9 x 4 + 27 x 2 27 = 9 x 2 x 3 Squaring both sides again 4 x 6 36 x 4 + 108 x 2 108 = 4 x 6 36 x 4 81 x 2 27 x 2 = 108 x = 2 Note that x 0 for x to be defined. \begin{aligned} \frac {x+\sqrt 3}{\sqrt x + \sqrt{x+\sqrt 3}} + \frac {x-\sqrt 3}{\sqrt x + \sqrt{x-\sqrt 3}} & = \sqrt x & \small \color{#3D99F6} \text{Let }a = x + \sqrt 3, \ b = x - \sqrt 3 \\ \frac a{\sqrt x + \sqrt a} + \frac b{\sqrt x - \sqrt b} & = \sqrt x \\ \frac {a(\sqrt x - \sqrt a)}{(\sqrt x + \sqrt a)(\sqrt x - \sqrt a)} + \frac {b(\sqrt x + \sqrt b)}{(\sqrt x - \sqrt b)(\sqrt x + \sqrt b)} & = \sqrt x \\ \frac {a(\sqrt x - \sqrt a)}{x-a} + \frac {b(\sqrt x + \sqrt b)}{x-b} & = \sqrt x & \small \color{#3D99F6} \text{Note that }x- a = - \sqrt 3, \ x-b = \sqrt 3 \\ \frac {a(\sqrt x - \sqrt a)}{-\sqrt 3} + \frac {b(\sqrt x + \sqrt b)}{\sqrt 3} & = \sqrt x \\ (b-a)\sqrt x + a\sqrt a + b\sqrt b & = \sqrt {3x} & \small \color{#3D99F6} \text{Note that }b- a = - 2\sqrt 3 \\ -2\sqrt{3x} + a\sqrt a + b\sqrt b & = \sqrt {3x} \\ a\sqrt a + b\sqrt b & = 3 \sqrt {3x} & \small \color{#3D99F6} \text{Squaring both sides} \\ a^3 + b^3 + 2ab\sqrt{ab} & = 27x & \small \color{#3D99F6} \text{Putting back }a = x + \sqrt 3, \ b = x - \sqrt 3 \\ (x+\sqrt 3)^3 + (x-\sqrt 3)^3 + 2(x^2-3)^\frac 32 & = 27x \\ 2x^3 + 18x + 2\sqrt{x^6-9x^4+27x^2-27} & = 27x \\ 2\sqrt{x^6-9x^4+27x^2-27} & = 9x - 2x^3 & \small \color{#3D99F6} \text{Squaring both sides again} \\ 4x^6-36x^4+108x^2-108 & = 4x^6 - 36x^4 - 81x^2 \\ 27x^2 & = 108 \\ \implies x & = \boxed{2} & \small \color{#3D99F6} \text{Note that }x \ge 0 \text{ for } \sqrt{x} \text{ to be defined.} \end{aligned}

Nice solution Sir, and much extended as well. I think we can shorten it as well. :)

Naren Bhandari - 3 years, 7 months ago

In the tenth line, it should be 2(x^2-3)^(3/2), but I think you accidentally multiplied them....

Veides Kasera - 3 years, 7 months ago

Log in to reply

Thanks. I missed a ^. You can actually key in as x^\frac 32 x 3 2 x^\frac 32 without the braces {}.

Chew-Seong Cheong - 3 years, 7 months ago

Log in to reply

No problem!

Veides Kasera - 3 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...